Inclusive Leadership in the Context of Wetland Ecology: Realizing Child Friendly Schools and Character Building for Elementary School Students - Fathul Jannah; Aslamiah Aslamiah (FKIP - Universitas Riau, 2026)
Inclusive education and leadership that is responsive to social diversity and the surrounding environment are increasingly recognized as essential elements in creating child friendly schools. In the context of wetland ecology which is a vital but often overlooked ecosystem in the educational curriculum, inclusive leadership plays an important role. This study aims to analyze the application of inclusive leadership in elementary schools located in wetland areas to create child friendly schools and instill character in students. This research identifies four main issues, namely, the role of inclusive leadership in creating child friendly schools in wetland areas; the application of inclusive leadership in character education; implementation challenges; and strategies that can be implemented by school principals to strengthen the implementation of child friendly schools and character education. The research uses a descriptive qualitative approach with a literature study method. The results of the study show that inclusive leadership is essential in integrating the values of diversity and environmental awareness in education in elementary schools located in wetland environments. The conclusion of this study is that inclusive leadership based on the ecological context of wetlands can be an effective model for creating child friendly schools and developing student character in primary schools.